RHEOLOGICAL, TEXTURAL AND PHYSICOCHEMICAL PROPERTIES OF BUCKWHEAT SOURDOUGH BREAD PREPARED WITH DIFFERENT LACTIC ACID BACTERIA STRAINS - Alkay, Zuhal; Alkay, Remziye; Dertli, Enes; Kokten, Kagan; Durak, M. Zeki (SLOVAK UNIV AGRICULTURE NITRA, 2023)
The aim of this study is to make buckwheat sourdough with three different lactic acid bacteria (LAB) strains and to determine its quality on wheat bread. After 24 hours fermentation, microbiological count, pH and TTA values and viscoelastic properties of buckwheat sourdoughs were examined. While the Limosilactobacillus fermentum 29GT-19 strain providing the highest value (109 CFU / g) in microbiological count, it was not observed in the chemically acidified control buckwheat dough. pH values changed from 3.8 to 4.6. The elastic modulus (G ') of all sourdoughs was found to be higher than the viscous modulus (G '') and a positive correlation was found between rheology graph with increase acidity. The prepared buckwheat doughs were then added to wheat flour as 10% and 20% (w / w). At the same time, commercial yeast bread was made as control bread. In the chemical composition of the breads, Levilactobacillus brevis KCO48 (dough with 20% buckwheat) sourdough bread had the highest ash content (1.26%) and moisture content. But mostly, the ash content of the breads was low, and the amount of moisture was higher than commercial yeast bread. The breads were generally found to have high crumb hardness (from 11.48 N to 31.34 N). As the concentration of buckwheat sourdough increased, the hardness of the bread increased. The lowest hardness (5.21 N) was determined in commercial yeast wheat bread. The results of this study have had a positive effect on the quality of wheat bread of buckwheat sourdough.
Keywords: LAB; buckwheat flour; sourdough; sourdough bread; rheology; GLUTEN-FREE BREAD; SHELF-LIFE; LACTOBACILLI; IMPACT; FLOUR; Food Science & Technology